PENGEMBANGAN MULTIMEDIA INTERAKTIF PADA PEMBELAJARAN RESENSI UNTUK PESERTA DIDIK KELAS XI SMAN 2 BANJARMASIN - Noor Asiah; Sainul Hermawan; Ahsani Taqwiem (LOCANA, 2024)
This study aims to describe the needs of students, the feasibility of interactive multimedia, and students' responses to interactive multimedia review text. This study used the Research and Development (R&D) method, with a 4-D research model consisting of define, design, develop, and disseminate stages. The results of this study indicate that 100% of class XI students at SMAN 2 Banjarmasin have a high level of need and are interested in using interactive multimedia in learning review texts. Through the research results it is known that the interactive multimedia that has been developed is rated "Very Eligible" with an overall percentage of 94% by material and media experts. While the results of the responses of students get a value of "Very Positive" with an overall percentage of 89%. Based on the results of research and development, it can be concluded that interactive multimedia in learning review text for class XI students is appropriate for use in learning.